High ratio bidirectional DC-DC converter with a synchronous rectification H-Bridge for hybrid energy sources electric vehicles - Zhang, Yun; Gao, Yongpin; Li, Jing; Sumner, M.; Wang, Ping; Zhou, Lei (Korean Institute of Power Electronics, 2016)
In order to match the voltages between high voltage battery stacks and low voltage super-capacitors with a high conversion efficiency in hybrid energy sources electric vehicles (HESEVs), a high ratio bidirectional DC-DC converter with a synchronous rectification H-Bridge is proposed in this paper. The principles of high ratio step down and step-up operations are analyzed. In terms of the bidirectional characteristic of the H-Bridge, the bidirectional synchronous rectification (SR) operation is presented without any extra hardware. Then the SR power switches can achieve zero voltage switching (ZVS) turn-on and turn-off during dead time, and the power conversion efficiency is improved compared to that of the diode rectification (DR) operation, as well as the utilization of power switches. Experimental results show that the proposed converter can operate bidirectionally in the wide ratio range of 3~10, when the low voltage continuously varies between 15V and 50V. The maximum efficiencies are 94.1% in the Buck mode, and 93.6% in the Boost mode. In addition, the corresponding largest efficiency variations between SR and DR operations are 4.8% and 3.4%. This converter is suitable for use as a power interface between the battery stacks and super-capacitors in HESEVs.